Information literacy in the digital age : an evidence-based approach - Welsh, Teresa S.; Wright, Melissa S. (Oxford, U.K. : Chandos Publishing, 2010)
This title details the various types of literacy that are important in the digital age of rapid technological change and information resources in a variety of formats. Each topic it addresses includes contextual background information, basic concepts, a resource list and activities to reinforce learning.
What is information literacy? -- Cultural literacy -- Library literacy : history, types, and roles -- Library literacy : information sources, classification systems -- Ethical literacy : scholarly communication and the academic code of conduct -- Network's literacy : database searching -- Computer literacy : computer hardware and software -- Network literacy : the Internet and the World Wide Web -- Media literacy and visual literacy -- Government literacy -- Financial literacy -- Writing a research paper -- Conclusion.
Includes bibliographical references and index.
Keywords: Information literacy; Information literacy; Informationskompetenz